Diversity at work : the practice of inclusion - Ferdman, Bernardo M.; Deane, Barbara (San Francisco, CA : Jossey-Bass, A Wiley Brand, 2014)
This book outlines the key issues involved in framing, designing, and implementing inclusion initiatives for organizations and groups. It offers ideas for helping individuals develop competencies for inclusion and shows how to apply the practices of inclusion by providing a unified model of employing diverse voices to address a range of related topics in multiple contexts. Examples of how diversity and inclusion have worked in a variety of settings are included. Topic experts, both internal and external change agents, and academics provide information. --
Includes index.
Includes bibliographical references at the end of each chapters and indexes.
Print version record and CIP data provided by publisher.
Keywords: Diversity in the workplace; Corporate culture; Personnel Management; Cultural Diversity; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Corporate culture; Diversity in the workplace; Electronic books; Electronic books